Mentors' Beliefs About Their Roles in Health Care Education: A Qualitative Study of Mentors' Personal Interpretative Framework. (October 2020) - Loosveld, Lianne M.; Van Gerven, Pascal W.M.; Vanassche, Eline; Driessen, Erik W.
Abstract : Purpose: How mentors shape their mentoring is strongly influenced by their personal beliefs about the goals and purpose of mentoring, the possible activities associated with it, who decides on the focus of the mentoring relationship, and the strategies mentors choose to enact these beliefs in practice. In accordance with the personal interpretative framework, the authors operationalized mentors' beliefs as professional self-understanding (the what) and subjective educational theory (the how) of teaching and sought to identify different mentoring positions. Method: Using a qualitative approach, the authors conducted semistructured interviews between December 2017 and January 2018 with 18 undergraduate mentors from Maastricht University in Maastricht, the Netherlands. The aim of the interviews was to reconstruct their personal interpretative framework. Before building a general pattern of explanation in a cross-case analysis, the authors performed a within-case analysis of the data, analyzing individual mentors. Results: This approach resulted in the identification and description of 4 mentoring positions: the (1) facilitator (service providing and responsive), (2) coach (development supporting and responsive), (3) monitor (signaling and collaborative), and (4) exemplar (service providing or development supporting and directive). Each position represents a coherent pattern of normative beliefs about oneself as a mentor (professional self-understanding) and how to enact these beliefs in practice (subjective educational theory). Conclusions: Awareness of their mentoring position can help mentors understand why they act the way they do in certain situations and how this behavior affects their mentees' learning and development. It can also help mentors identify personal learning needs and, consequently, provide opportunities for faculty development. Abstract : Supplemental Digital Content is available in the text.